Strategies to improve knowledge sharing in trading construction organization - Lee, Angela Siew Hoong *; Lim, Tong Ming * (IT in industry, 2017)
In this present economy that is wholly centered on knowledge and skill, knowledge sharing (KS) is gradually regarded as an important factor in organizational effectiveness and an innovative mechanism to cope with challenges [1]. Therefore, for organizations to create new knowledge sharing strategies are essentials to align to the knowledge economy to overcome business challenges [2, 3]. A preliminary investigation was conducted by focusing on the Critical Success Factors (CSF) to promote knowledge sharing at the organizational level and to examine the employees’ perception towards the types of knowledge sharing tools in the construction trading industry. This paper proposes several dimensions for knowledge strategy to manage knowledge assets that can be used as the key foundation to many organizations to